Analiza parametrów pracy krajowych kopalń węgla brunatnego - Kasztelewicz, Zbigniew (Wydawnictwa AGH, 2011)
The article presents a comparison of numerous parameters describing the operation of Polish lignite mines. Coal production and overburden stripping, overburden to coal ratio, the amounts of water pumped out, water to coal ration and employment were analyzed. An analysis and comparison of capacity, time of malfunctions, energy consumption and age structure was also conducted. To summarize the article, a comparison of chosen parameters of Polish and German BCS systems was performed.

W artykule dokonano porównania szeregu parametrów pracy kopalń odkrywkowych węgla brunatnego w Polsce. Analizie poddano: wydobycie węgla i zdejmowanie nadkładu, wskaźnik N:W, ilość wypompowanej wody, wskaźnik zawodnienia i zatrudnienie. Dokonano również analizy i porównania wydajności, czasu trwania awarii, energochłonności urabiania i struktury wiekowej koparek wielonaczyniowych. Podsumowując analizę dokonano porównań krajowych i niemieckich wybranych parametrów pracy układów KTZ.
Analysis of operating parameters of domestic lignite mines
Górnictwo i Geoinżynieria
Bibliogr. s. 118.
Keywords: lignite; węgiel brunatny; bucket wheel excavators; koparki wielonaczyniowe; open pit mining; ktz; bcs systems; górnictwo odkrywkowe